Acoustic Impedance Application of Petrophysical Assessment of Facha Reservoir (Lower Eocene), western Sirte Basin-Libya (Case Study) - Ghawar, Bahia M. Ben; Salloum, Fathi M.; Almarimy, Mohamed H.; Gheblawi, Mohamed S. (Iraqi Journal of Science, 2026)
Integration between acoustic impedance (AI), and petrophysical and mechanical properties of reservoir rocks provides a significant and substantial interpretation of lithology and fluid type discrimination in oil fields. An application of AI to define lithology, fluid type, and diagenetic history processes of Facha reservoir (Gir Formation, Lower Eocene) quality Dahab Oil Field in Western Sirte Basin, Libya. Thus, analyzing the data from three oil wells to calculate the reservoir properties: porosity (ø), water saturation (Sw), velocity ratio (Vp/Vs), Poisson’s ratio (PR), and AI. Cross-plots of Vp/Vs – AI, Bulk density (ρb) – AI and PR – AI with the ø and Sw influence illustrate four rock compounds of the Facha reservoir. Meanwhile, high AI values correspond to high Sw, which is restricted to the anhydrite and low porosity limestone lithology intervals. Also, increasing the porosity is followed by decreasing the AI with less than 50% of the Sw (hydrocarbon saturation). Although dolomitization, fracturing and blocky cementation are part of the geological history of the reservoir, they have not been discovered by the acoustic impedance.